2017
DOI: 10.1161/circheartfailure.117.004082
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Phenotyping of Pulmonary Hypertension in Left Heart Failure

Abstract: ABSTRACT:Increased pulmonary venous pressure secondary to left heart disease is the most common cause of pulmonary hypertension (PH). The diagnosis of PH due to left heart disease relies on a clinical probability assessment followed by the invasive measurements of a mean pulmonary artery pressure (PAP) ≥25 mm Hg and mean wedged PAP (PAWP) >15 mm Hg. A combination of mean PAP and mean PAWP defines postcapillary PH. Postcapillary PH is generally associated with a diastolic pulmonary pressure gradient (diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 78 publications
7
91
1
2
Order By: Relevance
“…Studies in patients with heart failure (HF) not related to AS [i.e. patients with HF with reduced or preserved left ventricular ejection fraction (LVEF)] have revealed two different haemodynamic patterns of PH with significantly different prognosis . The most common form is isolated post‐capillary PH (IpcPH), i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in patients with heart failure (HF) not related to AS [i.e. patients with HF with reduced or preserved left ventricular ejection fraction (LVEF)] have revealed two different haemodynamic patterns of PH with significantly different prognosis . The most common form is isolated post‐capillary PH (IpcPH), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…PH solely driven by elevated left‐sided filling pressures and defined by an elevated mean pulmonary artery wedge pressure (mPAWP) but a normal pulmonary vascular resistance (PVR) and diastolic pressure gradient (DPG) . Ten to 15% of patients, however, have combined pre‐ and post‐capillary PH (CpcPH), which is characterized by high filling pressures in combination with a pulmonary vascular component of PH and is defined by the combination of elevated mPAWP and PVR and/or DPG . This form of PH shares similarities with pulmonary arterial hypertension (PAH) and is associated with poor prognosis …”
Section: Introductionmentioning
confidence: 99%
“…PVR is variable in individuals with LV dysfunction, and previous studies have reported such variability to be independent of LVEF, which further complicates the pathophysiology of pulmonary hypertension in LV dysfunction. Although previous studies have reported that pulmonary hypertension is an important predictor of mortality in HF, the contribution of high ePASP to mortality may differ with age. The present study suggests that the prognostic value of high ePASP in individuals with HF increases with age.…”
Section: Discussionmentioning
confidence: 87%
“…No consideration is given to concomitant Ipc‐PH or Cpc‐PH, and given worse outcomes in the Cpc‐PH16 subgroup, we felt it important to explore the magnitude of pressure response. Furthermore, a priori knowledge of anticipated pressure reduction based on phenotype may assist in daily management and how best to titrate medical therapy.…”
Section: Discussionmentioning
confidence: 99%